UTILIZING VLOG IN YOUTUBE TO INCREASE STUDENTS’ INTERESTING IN SPEAKING ENGLISH LEARNING AT THE FIRST SEMESTER STUDENTS’ OF ENGLISH LANGUAGE EDUCATION UNIVERSITAS ISLAM SYEKH YUSUF - Isnaniah Isnaniah (LPPM Universitas Negeri Jakarta, 2020)
This study aims to find out how Youtube contributes the development of students’ speaking English skill. The design used in this research was one group pretest and posttest. The population of this research is all of the students at the first semester of english language education in the academic year 2019/2020 which the accessible population is 84 students while the sample of this research was 30 students. It took by using purposive sampling technique because the writer chose the sample based on proficiency and the sample is suitable for the purpose of the research. The data collected in this reseasrch is quantitative data. The writer used a test to collect the data. Then, to know the noramility and homogeneous distribution or not, the writer used the normality and homogeneity test. From the result of test normality showed that significant value of pretest was 0.047, while the significant of value of post-test was 0.000. It means that the data is not normal distribution, it was because the significant value of post-test 0.000 were less than 0.05. The result of homogeneity showed that the significant score was .026. based on the testing criteria significant score < 0.05. It means the data is not same variant group. Therefore, the test of data hypothesis, the writer used non-parametic test, Mann Whitney test. Its result of test showed that significance score .000 was smaller than probability score 0.05. It was concluded that accepted. In other words there was a significant positive effect of using youtube as media to improve students; speaking english skill.